Analyzing the Dimensions of Higher Education in Balochistan: A Student-Centric Approach - Zahra, Sadia; Haider, Saqlain (Journal of Development and Social Sciences, 2025)
This study examines the quality of higher education in Balochistan by analyzing student engagement, available facilities, and lecturer performance. Higher education in the region faces significant challenges, as students express dissatisfaction with their learning experience, institutional infrastructure, and faculty performance, which hinder academic growth and limit their potential contributions to society. A comprehensive survey was conducted among higher education students to evaluate their engagement, access to facilities, and perceptions of lecturer performance, alongside a review of student evaluation documents to assess faculty suitability. The findings reveal widespread dissatisfaction among students due to inadequate infrastructure, lack of facilities, and a mismatch between faculty expertise and teaching strategies. Immediate interventions are needed to improve the quality of higher education in Balochistan, including modernizing teaching methods, upgrading infrastructure, and hiring competent educators. Such measures are vital to empowering students to excel academically and make meaningful contributions to society.